A shift of brain network hub after spinal cord injury - Matsubayashi, Kohei; Shinozaki, Munehisa; Hata, Junichi; Komaki, Yuji; Nagoshi, Narihito; Tsuji, Osahiko; Fujiyoshi, Kanehiro; Nakamura, Masaya; Okano, Hideyuki (Frontiers in Molecular Neuroscience, 2023)
Background] Spinal cord injury (SCI) causes severe sequelae and significant social loss, depending on the extent of the damage. Most previous studies have focused on the pathology of the spinal cord to develop treatments for SCI. However, it is now known that the brain, which is not directly damaged, also undergoes morphological changes after spinal cord injury, which could affect natural recovery and treatment. In recent years, magnetic resonance imaging (MRI) has been developed to analyze functional changes in the brain. Restingstate functional MRI (rsfMRI), which captures brain activity at rest, can calculate functional connections between brain areas and identify central hubs by network analysis.[Purpose] We aim to investigate functional connectivity in the brain using rsfMRI after SCI and to determine how brain-network main hubs change over time.[Methods] We evaluated rsfMRI in ten mice of the contusional SCI model and calculated connectivity using graph theory. We evaluated "centrality", a representative parameter of network analysis. The subtype of centrality was degree centrality, which indicates the hub function of a single area. The five times of rsfMRI were performed in each individual mouse: before injury and at 1, 3, 7, and 14 weeks post-injury.[Results] Before the injury, the degree centralities of the primary and secondary motor cortex were high, suggesting that these motor cortices served as main hubs for motor function. After SCI, the hub function of the motor cortices decreased by 14 weeks. In contrast, hub function in the external capsule and the putamen comparatively increased with time after injury, suggesting that the extrapyramidal/subcortical system, which runs the ventral side of the spinal cord and remains after injury in this model, becomes dominant.[Conclusions] We demonstrated the shift of the brain network hub after SCI. The results of this study provide basic information for understanding brain network changes after SCI and would be useful for treatment selection and evaluation of its efficacy in SCI patients.